Spin-orbit coupling effects in BrO- and HOBr photodissociation reactions - Khomenko, Elena (Publishing House of Lviv Polytechnic National University, 2014)
Potential energy curves of the ground and a few excited states of the BrO- and HOBr along the photodissociation reactions, which correlate with lower dissociation limits are obtained on the base of calculations results by ab initio method. The singlet-triplet nonadiabatic transition with dissociation of the ground Х1S+ state to lower limit О(3Р) + Br-(1S) is predicted on the basis of calculations results. The ground singlet Х1S+ state of the BrO- has predissociative and metastable character for the upper vibrational levels. It is shown that the singlet-triplet transition to the lower triplet state a3A²¬X1A¢ is responsible for a weak HOBr absorption in the visible region (440–650 nm).На основі результатів розрахунку методом ab initio одержано криві потенціальної енергії для основного та ряду збуджених станів BrO- і HOBr в ході реакції фотодисоціації, що корелюють з нижніми межами дисоціації. За результатами розрахунку передбачено синглет-триплетний неадіабатичний перехід з дисоціацією основного Х1S+ стану до нижньої межі О(3Р) + Br-(1S). Основний синглетний стан йону Х1S+ BrO- є переддисоціативним і метастабільним для верхніх коливальних рівнів. Показано, що синглет-триплетний перехід до нижчого триплетного стану a3A²¬X1A¢ в молекулі HOBr відповідає за слабке поглинання у видимій області (440–650 нм).
Ефект спін-орбітальної взаємодії в реакціях фотодисоціації BrO- і HOBr
Keywords: photodissociation; singlet-triplet transition; spin-orbit coupling; absorption bands; spectrum; фотодисоціація; синглет-триплетний перехід; спін-орбітальна взаємодія; смуги поглинання; спектр